Superhydrophobic and superhydrophilic surface-enhanced separation performance of porous inorganic membranes for biomass-to-biofuel conversion applications. Issue 3 (11th February 2017) - Hu, Michael Z.; Engtrakul, Chaiwat; Bischoff, Brian L.; Jang, Gyoung G.; Theiss, Timothy J.; Davis, Mark F.
ABSTRACT: A new class of porous membranes is introduced to provide unique separation mechanisms by surface interactions and capillary condensation. High-performance architectural surface selective (HiPAS) membranes were designed for high perm-selective flux and high-temperature tolerance for hot vapor processing and liquid processing. Due to surface-enhanced selectivity, larger-fluxes were achieved by utilizing larger pore sizes (~8 nm for vapor phase and micron-sized pores for liquid phase separations). This article describes a membrane-based separation concept for biomass conversion pathways and demonstrates the initial data for selective permeation of toluene–water and toluene–phenol–water relevant to biofuel processing.